Disinformation by design: The use of evidence collages and platform filtering in a media manipulation campaign - Krafft, PM; Donovan, J (Taylor & Francis (Routledge), 2020)
Disinformation campaigns such as those perpetrated by far-right groups in the United States seek to erode democratic social institutions. Looking to understand these phenomena, previous models of disinformation have emphasized identity-confirmation and misleading presentation of facts to explain why such disinformation is shared. A risk of these accounts, which conjure images of echo chambers and filter bubbles, is portraying people who accept disinformation as relatively passive recipients or conduits. Here we conduct a case study of tactics of disinformation to show how platform design and decentralized communication contribute to advancing the spread of disinformation even when that disinformation is continuously and actively challenged where it appears. Contrary to a view of disinformation flowing within homogeneous echo chambers, in our case study we observe substantial skepticism against disinformation narratives as they form. To examine how disinformation spreads amidst skepticism in this case, we employ a document-driven multi-site trace ethnography to analyze a contested rumor that crossed anonymous message boards, the conservative media ecosystem, and other platforms. We identify two important factors that filtered out skepticism and contested explanations, which facilitated the transformation of this rumor into a disinformation campaign: (1) the aggregation of information into evidence collages—image files that aggregate positive evidence—and (2) platform filtering—the decontextualization of information as these claims crossed platforms. Our findings provide an elucidation of “trading up the chain” dynamics explored by previous researchers and a counterpoint to the relatively mechanistic accounts of passive disinformation propagation that dominate the quantitative literature. We conclude with a discussion of how these factors relate to the communication power available to disparate groups at different times, as well as practical implications for inferring intent from social media traces and practical implications for the design of social media platforms.